Tanggung Jawab Hukum Orang Tua Angkat yang Bercerai Terhadap Anak Angkat Menurut Undang-Undang Nomor 23 Tahun 2002 Tentang Perlindungan Anak (Studi Putusan Nomor 1294/Pdt.G/2015/Pa.Mks) - Tinambunan, Ignasia (Multiverse: Open Multidisciplinary Journal, 2023)
This qualitative study examines the responsibility of adoptive parents towards adopted children during divorce, the legal protection for adopted children in such situations, and analyzes Decision Number 1294/Pdt.G/2015/PA Mks. Adoptive parents, according to Islamic Law, should not sever the lineage/blood relationship with the biological parents, as adoption represents a humanitarian mission grounded in faith. Government Regulation Number 54 of 2007 sets conditions for child adoption, requiring prospective adoptive parents to possess economic and social capabilities to ensure proper care and education. In civil law, divorced adoptive parents remain responsible for the child's well-being until adulthood. Adopted children are protected in their rights, even in the event of divorce. The court's decision in Case Number 1294/Pdt.G/2015/PA Mks, granting custody to the mother, aligns with Islamic Law (Article 105). Divorce should be a last resort, with alternative solutions sought to protect children. Strengthening laws and regulations on child adoption is crucial to prevent broad interpretations. The government should provide counseling on the importance of registering adopted children's identities for their rights as Indonesian citizens. Judges should consider age-specific living arrangements for children, recognizing differing financial needs based on age